Method for Selecting an Engagement Index for a Specific Type of Game Using Cognitive Neuroscience. (18th August 2020) - Biercewicz, Konrad; Borawski, Mariusz; Duda, Jarosław
Abstract : The popularity of video games means that methods are needed to assess their content in terms of player satisfaction right from the production stage. For this purpose, the indicators used in EEG studies can be used. This publication presents a method that has been developed to determine whether a person likes an arcade game. To this end, six different indicators to measure consumer involvement in a video game using the EEG were compared, among others. The study was conducted using several different games created in Unity based on the observation (n = 31 ) of the respondents. EEG has been used to select the most suitable indices studied.